Property rights from below : commodification of land and the counter-movement - Schutter, Olivier de; Rajagopal, Balakrishnan (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"As formerly community-owned land and natural resources are privatized and titling schemes proliferate, Property Rights from Below questions the trend towards treating land as a commodity and explores alternatives to the Western model"--
OCLC-licensed vendor bibliographic record.
Keywords: Personal property; Natural resources -- Government policy; Land use; Community development; BUSINESS & ECONOMICS / Real Estate; LAW / Land Use; TECHNOLOGY / Construction / General